A CASE OF PANCREATICODUODENAL ARTERY ANEURYSM WITHOUT STENOSIS OR OBSTRUCTION OF CELIAC ARTERY - TOKURA, Masaaki; KAWASAKI, Shigeru (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2002)
Pancreaticoduodenal artery aneurysms are relatively rare. Half of the aneurysms are caused by stenosis or obstruction of the celiac artery except infection, pancreatitis, atherosclerosis and others. It has been thought that much blood flow to the celiac artery from superior mesenteric artery via pancreaticoduodenal artery and weakness of this artery cause aneurysms. We experienced a case of pancreaticoduodenal artery aneurysm without stenosis or obstruction of the celiac artery. Enlarged pancreaticoduodenal artery reduced to normal size after an embolization of the aneurysm and this artery, and a shunt flow to the celiac artery from superior mesenteric artery disappeared after the embolization of the arc of Buhler. From above findings, it is thought that the shunt flow via arc of Buhler increases blood pressure gradient between celiac artery and superior mesenteric artery, and induces dilatation and aneurysm formation by more pressure gradient and much blood flow to the pancreaticoduodenal artery. Embolization of both the arc of Buhler and pancreaticoduodenal artery aneurysm are necessary for treatment. Interventional radiology with a microcatheter is thought to be a non-invasive valuable method.